2013
DOI: 10.1038/ng.2669
|View full text |Cite
|
Sign up to set email alerts
|

The Capsella rubella genome and the genomic consequences of rapid mating system evolution

Abstract: 3 1 l e t t e r sThe shift from outcrossing to selfing is common in flowering plants 1,2 , but the genomic consequences and the speed at which they emerge remain poorly understood. An excellent model for understanding the evolution of self fertilization is provided by Capsella rubella, which became self compatible <200,000 years ago. We report a C. rubella reference genome sequence and compare RNA expression and polymorphism patterns between C. rubella and its outcrossing progenitor Capsella grandiflora. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
410
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 383 publications
(445 citation statements)
references
References 41 publications
23
410
2
2
Order By: Relevance
“…Two were consistent with rearrangement between the A. lyrata and A. arenosa genomes. One of these was also confirmed by the karyotypes of several of our dosage variants ( Figure 7B, inset) and was also detected in a population of Capsella rubella (Slotte et al, 2013). Taken together, these results suggest that it might originate from erroneous assembly of that particular segment of the A. lyrata genome (Slotte et al, 2013).…”
Section: Genomic Structure Of the A Suecica Genomesupporting
confidence: 68%
See 1 more Smart Citation
“…Two were consistent with rearrangement between the A. lyrata and A. arenosa genomes. One of these was also confirmed by the karyotypes of several of our dosage variants ( Figure 7B, inset) and was also detected in a population of Capsella rubella (Slotte et al, 2013). Taken together, these results suggest that it might originate from erroneous assembly of that particular segment of the A. lyrata genome (Slotte et al, 2013).…”
Section: Genomic Structure Of the A Suecica Genomesupporting
confidence: 68%
“…One of these was also confirmed by the karyotypes of several of our dosage variants ( Figure 7B, inset) and was also detected in a population of Capsella rubella (Slotte et al, 2013). Taken together, these results suggest that it might originate from erroneous assembly of that particular segment of the A. lyrata genome (Slotte et al, 2013). Only the third rearrangement was consistent with an inversion between the two parental genomes (A. arenosa Care-1 and A. suecica Sue-1).…”
Section: Genomic Structure Of the A Suecica Genomesupporting
confidence: 67%
“…We used nucleotidenucleotide BLAST 2.2.29 þ 58 , specifically the megablast algorithm 38 , to search ARTICLE NATURE COMMUNICATIONS | DOI: 10.1038/ncomms7338 the predicted coding sequence databases from A. lyrata 39 , C. rubella 40 and B. rapa 41 with the A. thaliana Col-0-coding sequences of RRS1, RPS4, RRS1B and RPS4B. Following the identification of putatively orthologous genes, MUSCLE 59 and CLUSTAL W 60 nucleotide and protein sequence alignments were used to generate phylogenetic trees using the Neighbour-Joining and Maximum Likelihood (Tamura-Nei model) methods, each with 1,000 bootstraps.…”
Section: Methodsmentioning
confidence: 99%
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms7338 ARTICLE A. thaliana. Using the nucleotide sequences of each gene from each pair in megablast searches 38 , we found that in the genomes of the sister species Arabidopsis lyrata 39 , and the closely related species Capsella rubella 40 , there are distinct putatively orthologous pairs matching both the 'A' pair (RRS1/RPS4) and 'B' pair (RRS1B/RPS4B). In A. lyrata, we also found an apparent duplication of the 'B' pair, resulting in a paralogous 'C' pair with a high level of identity to the 'B' pair (Fig.…”
Section: Avrrps4mentioning
confidence: 99%
“…An example script with all program versions and flags used for bioinformatic analyses, filtered vcf files, and a collated dataset and scripts used to identify genomic predictors of ASE are available on Figshare: https://doi.org/10.17045/sthlmuni.c.3654650. structure (20) and a large, stable effective population size (21,22). Indeed, selection on both protein-coding (23) and regulatory regions (18) is highly efficient in C. grandiflora, and high levels of polymorphism enhance the power to detect cis-regulatory variation and quantify selection.…”
Section: Significancementioning
confidence: 99%